Tradisi Perhitungan Weton Sebagai Penentuan Hari Pernikahan pada Masyarakat Suku jawa di Desa Wonorejo Kabupaten Luwu Timur - HS, Trio Meinarsono; Abdain (Fakultas Syariah IAIN Madura, 2023)
This study aims to determine the tradition of calculating weton as the determination of the wedding day in Javanese society in terms of Islamic law. This research is an empirical normative research approach, namely by conducting research in practice in the field. The research data was generated through interviews. The results of the study show that the tradition of calculating the weton in determining the auspicious day of marriage in Wonorejo Village, which is calculated before the application is intended to determine the suitability of the prospective husband and wife. The calculation of the weton becomes the final benchmark as a determinant of good and bad days at marriage by looking for compatibility or equality of the number of days based on the traditions of the surrounding community. Then the view of the community in carrying out the weton tradition is that there is no compulsion or obligation to follow this tradition, for those who do not want to follow it do not it's okay if you don't use the weton tradition because it goes back to the beliefs of each person. Furthermore, the view of the religious shop is that the weton tradition is permissible, as long as it does not conflict with religious norms. However, if in the weton tradition there are violations against religion, let alone leading to siltation and confusion of faith, then this is not permissible